2011
DOI: 10.1021/jf2030665
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of the Plant-Derived Compounds 23-Methyl-6-O-desmethylauricepyrone and (Z,Z)-5-(Trideca-4,7-dienyl)resorcinol and Their Synergy with Antibiotics against Methicillin-Susceptible and -Resistant Staphylococcus aureus

Abstract: The present study investigated the antibacterial activity of two plant-derived compounds, 23-methyl-6-O-desmethylauricepyrone (1) and (Z,Z)-5-(trideca-4,7-dienyl)resorcinol (2), and their synergistic effects with erythromycin and gentamicin against methicillin-susceptible (MSSA) and gentamicin- and methicillin-resistant Staphylococcus aureus (MRSA). Studies of the individual antibacterial activity of each plant-derived compound and synergy experiments were carried out, by the microdilution test in agar and by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…All of these compounds have a recognized antimicrobial activity (Ong and Khoo ; Machado et al, ; Taguri et al, ; Howell and D'Souza ) and a significant activity against Gram‐positive bacteria, alone or in combination with antibiotics (Hancock et al, ; Eumkeb et al, ; Joray et al, ). However, this is the first time that the potential antimicrobial synergic effects have been studied in depth among these compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these compounds have a recognized antimicrobial activity (Ong and Khoo ; Machado et al, ; Taguri et al, ; Howell and D'Souza ) and a significant activity against Gram‐positive bacteria, alone or in combination with antibiotics (Hancock et al, ; Eumkeb et al, ; Joray et al, ). However, this is the first time that the potential antimicrobial synergic effects have been studied in depth among these compounds.…”
Section: Resultsmentioning
confidence: 99%
“…All of these proportions are close to those of the pure compounds showing synergic behavior (Table ); therefore, this could explain the strong antimicrobial activity of the complete extract. The FICI values for the synergic mixtures found in the present study are similar to those previously reported for synergic combinations between antibiotics and essential oils (Rosato et al, ; Joray et al, ) or ellagitannins (Hussin and El‐Sayed ), suggesting that the synergic interactions between the C. salviifolius polyphenols are relevant. In agreement with our results, it has also been postulated that the potent antibacterial capacity of the pomegranate extracts might be due to the potential synergistic action of ellagitannins, anthocyanins (pelargonidin‐3‐galactose and cyanidin‐3‐glucose), and flavonols (quercetin and MY) (Howell and D'Souza ).…”
Section: Resultsmentioning
confidence: 99%
“…Surprisingly, these complexes show higher antimicrobial properties than individual compounds. Testing of compounds and complexes was performed by the use of basic microbiological methods, method of determination of growth dependences (“growth curves”) [7678], where the minimal concentrations of tested compounds inducing inhibition of growth-minimum inhibitory concentration (MIC) [79] and total inhibitory concentration (TIC) [80] are determined, or method based on the determination of inhibition zones [81–83]. Measuring inhibition zones was the first test to the antimicrobial properties of the compounds of interest.…”
Section: Resultsmentioning
confidence: 99%
“…The time sensitivity assay was determined according to the previous report [19]. The tested sample solutions including distilled water and LB broth (1:1, v/v) with the final concentrations ranging from 1× MIC to 4× MIC were inoculated with bacteria suspensions (nearly 10 5 CFU/mL) in triplicate at 37 • C for 24 h with shaking.…”
Section: Time-kill Analysismentioning
confidence: 99%